Coping Strategy In Adolescent Victims Of The Kanjuruhan Tragedy - Ahsan, A. Afifuddin; Hartanto, Agit Purwo; Hafidzoh, Hafidzoh (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
The Kanjuruhan tragedy in 2022 led to hundreds of victims, including adolescents. This tragedy left serious impacts, both physical and psychological. Psychologically, the victim experienced post-traumatic stress. This article describes stress factors, forms of stress, and coping strategies of the Kanjuruhan tragedy survivors. The case study implemented a qualitative approach. Data were collected via in-depth interviews with three male adolescents who survived the tragedy. These informants reported symptoms of stress after the incident. In dealing with this stress, the informants used various methods which included problem-focused and emotion-focused coping. Apart from that, the informants also grew closer to God, indicating spiritual-focused coping. This study can be used as a reference for people who experience traumatic events to apply the appropriate coping strategies.